Dinâmica da estrutura microbiana em solos de Campos Nativos (Bioma Mata Atlântica): comparação metagenômica entre áreas de uso agrícola, restauração e preservação - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2024)
The expansion of agricultural practices has caused degradation in several terrestrial ecosystems, due to the intensification of land use and conversion of native ecosystems into agroecosystems. These practices impact the structuring of soil microbial communities and, consequently, the ecosystem services provided by the soil microbiota. The Campos Gerais in Paraná, composed of extensive areas of native grassland vegetation, can be considered fragile due to exposure to abiotic factors, exclusion from public conservation policies, and intense pressure from agriculture and silviculture. Ecological restoration practices are an alternative for recovering native grassland areas degraded by anthropic actions. However, the impact that land use changes have on the microbial communities of these ecosystems is still poorly understood. For this reason, high throughput sequencing and comparative metagenomics were used to verify this composition of the taxonomic and functional microbial communities in soils from native fields with different use histories: (1) agricultural area, (2) restoration area passive ecological since 2017 and (3) native area in a preservation unit. The results show that the bacterial community of the agricultural area, followed by the restoration area, present the highest Shannon diversity index values that were significantly different from the preservation area. The assessment of the taxonomic composition of the areas revealed that phyla considered copiotrophic, such as Pseudomonadota, were more abundant in the environment in the preservation area, whereas oligotrophic phyla like Acidobacteria were more abundant in the agricultural area, in contrast, the abundance of these phyla in the restoration area decreased. The Archaea community did not show differences in Shannon index and Pielou equitability and, therefore, were more resilient to land use changes. The fungal diversity was higher in the preservation area and was significantly distinct from the agricultural area, while the restoration area was more similar to the preservation area. The beta diversity analysis calculated by the Bray-Curtis dissimilarity indicates that passive ecological restoration for five years has caused changes in the soil microbial community. Furthermore, the agricultural and restoration areas showed a greater amount of differentially abundant functional genes when compared to the preservation area, which may be responses to greater disturbances in these environments. In a principal component analysis (PCA) where PC1 was responsible for 32,6% of the variation, it was evidenced that the functional diversity found in the agricultural area is farther from the preservation area, and the restoration area is in an intermediate position, showing that the functional composition was also affected by the history of land use. These results indicate that the microbial community of anthropized soils of native fields already shows recovery of its structure in just five years of passive restoration, highlighting the importance of restoration and conservation practices of the ecosystems of Campos Gerais in Paraná.
Keywords: Diversidade microbiana; Histórico de uso do solo; Restauração; Ecossistema de Campo; Metagenômica; Microbial diversity; Land use history; Restoration; Field ecosystem; Metagenomics; CNPQ::CIENCIAS BIOLOGICAS